Risk Factors for Pneumonia in Toddlers During the Covid-19 Pandemic - Yusya, Fitri; Masrizal, Masrizal; Haq, Arinil; Markolinda, Yessy (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: Among the period 2019-2021, Ambacang Health Center has the highestfrequency of pneumonia in toddlers in Padang CityPurpose: This study aims to determine thefactors associated with pneumonia in toddler in the Ambacang Public Health CenterWork Area, Padang City, during COVID-19 pandemic.Methods: Study used a case-control design with similar age groups. Population of toddler aged 11-59months. Cases were sampled using a simple random sampling technique based on pneumonia registration in March 2020-March 2022, controls were sampled usingpurposive sampling. Interviews and questionnaires were used to collect data, whichwas then analyzed using univariate, bivariate, and multivariate analysis. Thenumberofsampleswas74toddlerwith37samplesforeachgroupResults: Thereisassociationbetweenexclusivebreastfeeding(OR=3.67),basicimmunization(OR=2.8), air pollution (OR=5.0) and residential density (OR=3.0) on the incidenceofpneumonia.Meanwhile,historyofLBW,educationlevelandmaternalemployment were not associated with pneumonia. Household air pollution was thedominantfactorassociatedwithincidenceofpneumonia for toddler during COVID-19 pandemic in the AmbacangPublic Health Center Work Area, Padang CityConclusion: It is recommended for health workersto improve health promotion PHBS in the household and impact air pollution on thehealthof toddler.